Securitary Text on Images with RC-128 Bit Synthric Key Encryption - Muslih Muslih; Abdussalam Abdussalam; Elkaf Rahmawan Pramudya (Journal of Applied Intelligent System, 2021)
The main purpose of using cryptography is to provide the following four basic information security services. One of the purposes of cryptography is secrecy. Confidentiality is the fundamental security service provided by cryptography. This is a security service that stores information from unauthorized persons. Confidentiality can be achieved through a variety of ways ranging from physical security to the use of mathematical algorithms for data encryption. Vernam cipher is a stream cipher where the original data or plain with 8x8 block operation. Experimental results prove that RC4 can perform encryption and decryption with a fast execution process. In this study used a processor with 8GB of RAM. The encryption result of the text used yields the average encryption time and decryption average of 2 second.